The altered metabolites contributed by dysbiosis of gut microbiota are associated with microbial translocation and immune activation during HIV infection - Zhang, Yu; Xie, Zhiman; Zhou, Jie; Li, Yanjun; Ning, Chuanyi; Su, Qisi; Ye, Li; Ai, Sufang; Lai, Jingzhen; Pan, Peijiang; Liu, Ningmei; Liao, Yanyan; et al. (Frontiers in Immunology, 2023)
Background: The immune activation caused by microbial translocation has been considered to be a major driver of HIV infection progression. The dysbiosis of gut microbiota has been demonstrated in HIV infection, but the interplay between gut microbiota and its metabolites during HIV infection is seldom reported. Methods: We conducted a case-controlled study including 41 AIDS patients, 39 pre-AIDS patients and 35 healthy controls. Both AIDS group and pre-AIDS group were divided according to clinical manifestations and CD4 + T cell count. We collected stool samples for 16S rDNA sequencing and untargeted metabolomics analysis, and examined immune activation and microbial translocations for blood samples. Results: The pre-AIDS and AIDS groups had higher levels of microbial translocation and immune activation. There were significant differences in gut microbiota and metabolites at different stages of HIV infection. Higher abundances of pathogenic bacteria or opportunistic pathogen, as well as lower abundances of butyrate-producing bacteria and bacteria with anti-inflammatory potential were associated with HIV severity. The metabolism of tryptophan and branched chain amino acids (BCAAs) was disordered after HIV infection. Lower level of anti-inflammatory metabolites and phosphonoacetate, and higher level of polyamines were observed during HIV infection. Moreover, microbiota-associated metabolites, such as B vitamins, L-tryptophan and BCAAs, were correlated to microbial translocation and immune activation, and microbial metabolic pathways related to these altered metabolites differed. Conclusions: Gut microbiota is associated with metabolites involved in immune activation and microbial translocation, suggesting that the interaction between microbiota and metabolites may implicate in intestinal barrier disruption HIV infective progression.